INDIRECT TAX COMPONENTS AND ECONOMIC GROWTH OF SELECTED AFRICAN COUNTRIES: PANEL AUTOREGRESSIVE DISTRIBUTED LAG APPROACH - Uche Okoro Orji (Journal of Management and Accounting)
This study tries to assess the causal link between components of indirect tax namely Value added tax and Custom and Excise Duties and economic growth measured using Real Gross Domestic Product. The study used panel data drawn from six (6) selected African countries namely Nigeria, Ghana, South Africa, Kenya, Egypt and Morocco from 2000 to 2018. These are countries within the African region that has a robust economy, broad gross domestic product and modernized business environment. Secondary data used were generated from World Bank World Development indicator, OECD data base on tax revenue in Africa and Central Bank of Nigeria. Quadratic match –Sum procedure was adopted in converting the annual data into quarterly data from E-views and the data are in their natural logarithm. Different econometric techniques were applied in the study while the data was analyzed by means of Autoregressive Distributed Lag (ARDL) Model using E views 10 and Stata version 16 packages. The study revealed that custom and excise duties had a positive and significant relationship with economic growth of selected African countries in the long run, while there is a positive but insignificant influence of custom and excise duties on economic growth of these countries in the short run. Also, the findings showed that there is no significant influence of Value added tax (VAT) on real GDP of the selected African countries in the long run; while Value added tax exhibited a positive though insignificant influence on real GDP in the short run in these countries. The study recommends among others that a conducive environment for entrepreneurship, tax incentives, and innovation must be offered, as well as job opportunities in order to increase these countries’ revenue bases, particularly through business and also these countries’ government should expand, nurture and sustain their value added tax and other tax bases in order to continue to support positive economic growth.